Slow & Low: The Story of the Kansas Ag. Pilot - Hallaq, Tom (Kansas State University, 2017)
This is the story of the Kansas ag. pilots told in their own words. Inspired by my own grandfather, this is a story for any Kansan with roots in the farmlands or wings in the sky.
Keywords: Aviation; Crop Dusters; Areal Applicators; Pilots; Agriculture; Kansas State University